Public Role in APBN Contributions - Ahmad Virman Haris; Khusnuddin (al-Afkar, Journal For Islamic Studies, 2025)
The public's role in supporting the State Budget (APBN) is vital as one of the main sources of state revenue. The public contributes directly through tax payments, including income tax, value-added tax, and regional taxes, and indirectly through economic activities that broaden the state's revenue base. This article aims to examine the public's contribution to the APBN by highlighting aspects of tax awareness, economic participation, and supportive government policies. The research was conducted using qualitative descriptive analysis with secondary data from various reports and academic studies. The results show that increasing public contributions to the APBN depends on public education, simplification of tax administration processes, and public service innovations such as tax digitization. The conclusion of this article emphasizes that collaboration between the government and the public is crucial in ensuring fiscal sustainability and national development.